PENGEMBANGAN PAPAN PANTUL PORTABEL DUA SISI BALIK UNTUK MEDIA PEMBELAJARAN TENIS MEJA - Muhammad Zaky; Alit Rahmat (Plyometric: Jurnal Sains dan Pendidikan Keolahragaan, 2026)
The research method employed was Research and Development (R&D), fully adopting the ten stages of the Borg and Gall model. Data collection was conducted through observation, interviews, and the administration of a five-point Likert scale closed-ended questionnaire to a team of expert validators and extracurricular student participants as direct users. The research results indicated that the product underwent three concrete revision phases, including reinforcing the stand base stability with carpet rubber, securing the rubber surface edges using black cloth tape, and modifying the corners into rounded shapes for safety. The cumulative empirical feasibility rate of the product in the final post-implementation evaluation successfully reached 91%, classifying it into the highly feasible category. In conclusion, the innovation of the full-scale portable reversible dual-surface rebound board proved to be effective, safe, and highly feasible for improving students' motor skill consistency in forehand and backhan drive attacks as well as short drop shot control without relying on complex digital components. This media serves as an economical and appropriate technological solution to address facility limitations and coach-to-student ratio gaps in the field.